A Modified Regimen of 21-day Nab-Paclitaxel Plus Gemcitabine in Locally Advanced or Metastatic Pancreatic Cancer: A Retrospective Real-World Study. (16th November 2022) - Chang, Chen; Meng, Lingwei; Li, Xiaofen; Cheng, Ke; Yi, Cheng; Peng, Bing; Ma, Ji; Cao, Dan
Background: It is 1 of the standard treatment options for metastasis pancreatic cancer to receive nab-paclitaxel (125 mg/m 2 ) plus gemcitabine (1000 mg/m 2 ) on days 1, 8 and 15 every 28 days. Some patients showed intolerance and inconvenience to this therapeutic regimen. Thus, we conducted this retrospective real-world study to determine the efficacy and tolerability of a modified 21-day nab-paclitaxel plus gemcitabine (nab-P/Gem) regimen for the first-line treatment of locally advanced or metastatic pancreatic cancer. Methods: Patients with locally advanced and metastatic pancreatic cancer treated with nab-paclitaxel (125 mg/m 2 ) plus gemcitabine (1000 mg/m 2 ) on days 1 and 8 every 21-day at West China Hospital and Shang Jin Hospital of Sichuan University from Mar 2018 to Dec 2021 were reviewed retrospectively. Clinical characteristics of patients were collected. The progression-free survival, overall survival, objective response rate, disease control rate, and toxicity were evaluated. Results: A total of 113 patients who received the modified regimen of 21-day nab-P/Gem chemotherapy were included. The median overall survival was 9.3 months and the median progression-free survival was 4.4 months. The objective response rate and disease control rate were 18.6% and 56.7%, respectively. The median relative dose intensity for this modified regimen was 65%. The adverse events were mild to moderate, and the most common grade 3 or 4 treatment-related adverse events were neutropenia (21%) and leukopenia (16%). Conclusions: Our study showed that this modified regimen of 21-day nab-P/Gem for locally advanced and metastatic pancreatic cancer had comparable efficacy and tolerable toxicity. This treatment may provide a considerable option for pancreatic cancer patients who desire a modified schedule. The modified regimen of 21-day nab-P/Gem is also an option worth considering during the coronavirus disease 2019 pandemic for minimizing the number of visits and limiting the risk of exposure.